Anti-Inflammatory Effect of Isolate Compounds from Ethyl Acetate Fraction of Piper crocatum Ruiz and Pav Leaves on Lipopolysaccharide-induced RAW 264.7 Cells - Nilda Lely; . Dachriyanus; Yufi Aldi; . Almahdy; Fatma Sri Wahyuni (HAYATI Journal of Biosciences, 2023)
Red betel (Piper crocatum Ruiz and Pav) is a traditional Indonesian plant. The ethyl acetate fraction of red betel leaf has the potential as an anti-inflammatory. This research aimed to determine the anti-inflammatory effect of isolate compound from ethyl acetate fraction of Piper crocatum leaves on the production of cytokine pro-inflammatory TNF-α and ICAM-1 in lipopolysaccharide-induced RAW 264.7 cells. Cell viability was determined by the MTT method in the concentration range of 1.25; 2.5; 5; 10; 20, and 40 µg/ml. The TNF-α and ICAM-1 level was determined by the TNF-α and ICAM-1 assay kit as measured by an ELISA plate reader. Cell viability test of isolate compound from ethyl acetate fraction, the concentrations that gave viability percentages above 80% were 10; 5; 2.5 and 1.25 ug/ml. Isolate compound at concentrations of 10, 5, 2.5 and 1.25 ug/ml significantly inhibited TNF-α and ICAM-1 production with p<0.05 (p = 0.000).